Gambaran Parental Burnout pada Orang Tua dengan Anak Autism Spectrum Disorder - Prasetyanti, Annisa Audrey; Widayat, Iwan Wahyu (Universitas Airlangga, 2024)
This research aims to describe the overview of parental burnout in parents with children with autism spectrum disorder. This research used intrinsic case through interviews, field notes, documents, artifacts. Data were analyzed by thematic analysis by Braun & Clarke. The results showed that all participants experienced parental burnout that was unique, but almost similar. The experiences are the experience of fatigue, the experience of inability, the experience of contrast, the experience of distance from children, and the experience of the Covid-19 pandemic. Parental burnout is caused by unbalanced risk and protective factors. These risk factors come from internal individuals, internal families, and external factors. Meanwhile, protective factors come from support and love for children. It has impact on oneself, family, children, and society. To overcome parental burnout, efforts are made related to individual relaxation efforts, individual learning efforts, relational efforts, and parenting efforts for children.